Survival of Antibiotic Resistant Bacteria and Horizontal Gene Transfer Control Antibiotic Resistance Gene Content in Anaerobic Digesters - Miller, Jennifer H.; Novak, John T.; Knocke, William R.; Pruden, Amy (Frontiers in Microbiology, 2016)
Understanding fate of antibiotic resistant bacteria (ARB) versus their antibiotic resistance genes (ARGs) during wastewater sludge treatment is critical in order to reduce the spread of antibiotic resistance through process optimization. Here, we spiked high concentrations of tetracycline-resistant bacteria, isolated from mesophilic (Iso M1-1- a Pseudomonas sp.) and thermophilic (Iso T10- a Bacillus sp.) anaerobic digested sludge, into batch digesters and monitored their fate by plate counts and quantitative polymerase chain reaction (QPCR) of their corresponding tetracycline ARGs. In batch studies, spiked ARB plate counts returned to baseline (thermophilic) or 1-log above baseline (mesophilic) while levels of the ARG present in the spiked isolate (tet(G)) remained high in mesophilic batch reactors. To compare results under semi-continuous flow conditions with natural influent variation, tet(O), tet(W), and sul1 ARGs, along with the intI1 integrase gene, were monitored over a 9-month period in the raw feed sludge and effluent sludge of lab-scale thermophilic and mesophilic anaerobic digesters. sul1 and intI1 in mesophilic and thermophilic digesters correlated positively (Spearman rho = 0.457 to 0.829, P<0.05) with the raw feed sludge. There was no correlation in tet(O) or tet(W) ratios in raw sludge and mesophilic digested sludge or thermophilic digested sludge (Spearman rho = 0.130 to 0.486, P = 0.075 to 0.612). However, in the thermophilic digester, the tet(O) and tet(W) ratios remained consistently low over the entire monitoring period. We conclude that the influent sludge microbial composition can influence the ARG content of a digester, apparently as a result of differential survival or death of ARBs or horizontal gene transfer of genes between raw sludge ARBs and the digester microbial community. Notably, mesophilic digestion was more susceptible to ARG intrusion than thermophilic digestion, which may be attributed to a higher rate of ARB survival and/or horizontal gene transfer between raw sludge bacteria and the digester microbial community.